ANTI-INFLAMMATORY, ANTIPYRETIC AND ANALGESIC ACTIVITIES OF CHLOROFORM EXTRACT OF ALOE BARBADENSIS MILLER IN ALBINO RATS - ALYAS, S; HABIB, R; SHAFIQUE, T; ZAHID, B; HAYAT, S; ILYAS, A; AHMAD, S; KHAN, RH (Biological and Clinical Sciences Research Journal, 2023)
The pharmacological activities of the leaf gel of Aloe vera have been extensively evaluated. Gel and latex are two basic products of aloe leaves. Latex and gel contain biologically active components. Polysaccharides contained in the leaf gel attribute most of the health benefits like anti-inflammatory, pain and fever, associated with aloe vera. In the present study, chloroform extract of A. barbadensis at various concentrations was investigated for its anti-inflammatory, antipyretic and analgesic activities in albino rats. Twenty-four albino rats were randomly divided into three groups (control, standard and experimental group). Division of groups was the same for all activities. Control and standard groups contain 4 rats in each group whereas experimental group contains 16. All the rats in three groups were treated with carrageenan to induce oedema, Brewer’s yeast to induce pyrexia and acetic acid to induce pain. The control group was treated with normal saline for all the activities. Standard group rats were treated with the reference drug diclofenac for anti-inflammatory and analgesic activities and paracetamol for antipyretic activity. Experimental group rats were given chloroform extract of A. barbadensis with 50, 100, 200 and 400mg/kg concentration. The result showed a significant inhibition (98%) in oedema at 3rd hour at the dose of 400mg/kg as compared to control group. For antipyretic activity, there was a significant reduction (66%) in pyrexia at 4th hour at the dose of 50mg/kg as compared to control group. And in analgesic model a significant reduction (64%) in the writhing at the dose of 400mg/kg as compared to control group. These results demonstrated that the chloroform extract of Aloe barbadensis miller have anti-inflammatory, antipyretic and analgesic activity and suggested its inhibitory actions on inflammation, fever and pain.